In Silico Insights into the Mechanism of Action of Epoxy-α-Lapachone and Epoxymethyl-Lawsone in Leishmania spp. - Juliana Figueiredo Peixoto; Adriane da Silva Oliveira; Patrícia Queiroz Monteiro; Luiz Filipe Gonçalves-Oliveira; Valter Viana Andrade-Neto; Vitor Francisco Ferreira; Franklin Souza-Silva; Carlos Roberto Alves (Molecules, 2021)
Epoxy-α-lapachone (Lap) and Epoxymethyl-lawsone (Law) are oxiranes derived from Lapachol and have been shown to be promising drugs for Leishmaniases treatment. Although, it is known the action spectrum of both compounds affect the Leishmania spp. multiplication, there are gaps in the molecular binding details of target enzymes related to the parasite’s physiology. Molecular docking assays simulations were performed using DockThor server to predict the preferred orientation of both compounds to form stable complexes with key enzymes of metabolic pathway, electron transport chain, and lipids metabolism of Leishmania spp. This study showed the hit rates of both compounds interacting with lanosterol C-14 demethylase (−8.4 kcal/mol to −7.4 kcal/mol), cytochrome c (−10.2 kcal/mol to −8.8 kcal/mol), and glyceraldehyde-3-phosphate dehydrogenase (−8.5 kcal/mol to −7.5 kcal/mol) according to Leishmania spp. and assessed compounds. The set of molecular evidence reinforces the potential of both compounds as multi-target drugs for interrupt the network interactions between parasite enzymes, which can lead to a better efficacy of drugs for the treatment of leishmaniases.